Morphological characteristics of the Goat Creole of the South of Mendoza, Argentina (Veterinary Science, 2020)
The objective of this work was to determine the values of zoometric variables that define the Creole Goat of South Mendoza (Mendoza province, Argentina). Samples were taken at commercial goat farms located in South and North regions and in seven locations of San Rafael and Malargue departments of Mendoza. Eight hundred and thirty five Creole goats were sampled, with ages from two teeth up to tooth cutter, using the method proposed by FAO (2000). The variables studied were Head width (HW), Head length (HL), Height to the end of Neck (HN), Thoracic perimeter (TP), Body length (BL), Rump width (RW); Height to the Rump (HR) and Shank Perimeter (SP). The variables were analyzed using multivariate techniques principal components, discriminants, canonical populations) and clusters based on Euclídeus distances and their graphic representation as dendrograms. The results showed that all variables followed a normal distribution. In turn, uniformity in the variables was found, since Coefficient of Variation was lower than 9% in all cases. The variables that best describe the model were HN, TP, RW, SP and HN, which represent 50% of the total data variability. The dendogram showed two mixed groups where variables of locations of North and South regions were found, finding the smallest eucledian distance among locations of the South region. The Figure of the Analysis of Principal Components showed that dispersion of the variables behaves in an homogeneous way, without generating groups or subpopulations. Variable homogeneity found in this work would allow to assume that the Creole Goats of theSouth Mendoza would  belong to a common genetic stem that would characterize them as members of a defined racial group.
Keywords: zoogenetic resource; Creole goat; zoometrics; phenotypic characterization